Structural and functional analysis of the small GTPase ARF1 reveals a pivotal role of its GTP-binding domain in controlling of the generation of viral inclusion bodies and replication of grass carp reovirus - Zhang, Jie; Li, Pengwei; Lu, Riye; Ouyang, Songying; Chang, Ming Xian (Frontiers in Immunology, 2022)
Grass carp reovirus (GCRV) is the most pathogenic double-stranded (ds) RNA virus among the isolated aquareoviruses. The molecular mechanisms by which GCRV utilizes host factors to generate its infectious compartments beneficial for viral replication and infection are poorly understood. Here, we discovered that the grass carp ADP ribosylation factor 1 (gcARF1) was required for GCRV replication since the knockdown of gcARF1 by siRNA or inhibiting its GTPase activity by treatment with brefeldin A (BFA) significantly impaired the yield of infectious viral progeny. GCRV infection caused the redistribution subcellular localizations of gcARF1, which was recruited by the nonstructural proteins NS80 and NS38 of GCRV into viral inclusion bodies (VIBs) through direct protein-protein interactions. The small_GTP domain of gcARF1 was confirmed to be crucial for promoting GCRV replication and infection, and the number of VIBs reduced significantly by the inhibition of gcARF1 GTPase activity. The analysis of gcARF1-GDP complex crystal structure revealed that the 27AAGKTT32 motif and eight amino acid residues (A27, G29, K30, T31, T32, N126, D129 and A160), which were located mainly within the GTP-binding domain of gcARF1, were crucial for the binding of gcARF1 with GDP. Furthermore, the 27AAGKTT32 motif and the amino acid residue T31 of gcARF1 were indispensable for the function of gcARF1 in promoting GCRV replication and infection. Taken together, it is demonstrated that the GTPase activity of gcARF1 is required for efficient replication of GCRV and that host GTPase ARF1 is closely related with the generation of VIBs.